Seed quality of crambe (Crambe abyssinica Hochst) submitted to different drying methods - Silva, Magnun Antonio; Lima, Juliana Joice; Biaggioni, Marco Antonio; Cavariani, Cláudio; Ferreira, Gisela (Revista Ciência Agronômica, 2016)
The objective of this research was to evaluate the effects of different drying methods on physiological quality of crambe seeds. Crambe seeds of FMS Brilhante cultivar were produced in the Lageado experimental farm (UNESP, Botucatu, Brazil) in 2012. The drying methods were: artificial drying with hot air, artificial drying with fresh air, natural yard drying, natural shade drying and natural field drying. The water content of seeds was monitored before, during and after drying. Germination, first germination count, abnormal seedlings, GSI, germination synchronization, frequency  and germination mean time, electrical conductivity, fatty acid index and oil content were evaluated in order to know the physiological quality. The experimental design was randomized and the averages compared by the t-test at 5% significance. Results showed that artificial hot air drying favored with higher germination and vigor of crambe seeds when compared to other drying methods and demanded shorter time to reduce the water content. The natural shade drying method is feasible for crambe seeds despite taking longer.